Expert System Diagnosing Diseases in Coffee Plants Using Certainty Factor Method - baringin sianipar; Preddy Marpaung (Marqcha Institute, 2021)
Diagnosing diseases in Arabica coffee plants using the Certainty Factor Method. Diagnosing diseases of Arabica coffee plants must be fast and precise in accordance with technological developments. Making this coffee plant disease diagnosis application aims to make it easier for coffee farmers or the public to find out the types of diseases in coffee plants and how to control them based on the symptoms of coffee plant diseases that are entered and an answer will come out, namely the name of the disease from the questions entered and how to control it. Expert systems are used as a tool to solve problems that are usually solved by an expert.